THE EFFECT OF INTERNSHIP EXPERIENCE AND EMOTIONAL INTELLIGENCE IN WORK READINESS OF GENERATION Z IN JABODETABEK - Aini, Siti Nur; Turangan, Joyce A. (International Journal of Application on Economics and Business, 2025)
Generation Z in Indonesia dominates the workforce and proficiency in digital skills. However, Generation Z faces challenges related to the perception of companies that view them as less prepared for work, which drives efforts from the government and educational institutions to enhance their work readiness. This study aims to analyze the effect of internship experience and emotional intelligence on the work readiness of Generation Z in Jakarta, Depok, Bogor, Tangerang, and Bekasi. This research uses a quantitative method with a survey of 150 respondents selected through non-probability sampling using a convenience sampling approach The study utilized a questionnaire for data collection, which was then analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM).. The results show that both internship experience and emotional intelligence have a positive and significant impact on work readiness. The findings indicate that internship experience has a greater effect on work readiness compared to emotional intelligence, highlighting the importance of strengthening internship programs to prepare Generation Z to meet labor market demands. This research provides benefits for Generation Z in the Jabodetabek area to determine strategies for enhancing work readiness through leveraging internship opportunities and developing emotional intelligence, both of which have proven to significantly help them face intense job competition and improve their chances of being hired by companies.